Preparation method of supercapacitor composite electrode material
Patent Information
- Application Number
- CN202311396991.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-10-26
AI Technical Summary
目前层状钴铁双金属氢氧化物电极材料在超级电容器的应用得到了广泛认可,其具有低成本、高丰度、环境友好等优点,但是低比电容和循环稳定性差限制了它的实际应用
[0034]1、磁场协同超声诱导优化电极结构:多物理场复合合成是要通过其复杂的耦合过程达到对层状钴铁基氢氧化物合成过程的有效调控,其复合效果超过简单的物理场叠加。采用外加磁场对层状钴铁基氢氧化物进行取向调控,设计并可控合成三维或中空纳米结构,通过改变外加磁场的方向、强度、频率等参数可控制氢氧化物的形貌和生长取向,增强自旋极化效果,扩大复合材料的结构设计空间,制备出结构稳定、比表面积大、倍率性能高的电极材料。超声场产生的独特微环境的空化泡可避免颗粒的团聚,分级的纳米结构可以避免粒子聚集,促进更多活性位点的暴露,可以快速高效的制备出具有独特结构和优良性能的纳米复合材料。
Smart Images

Figure CN117275960B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials preparation technology, specifically relating to a method for preparing a supercapacitor composite electrode material. Background Technology
[0002] Supercapacitors have attracted much attention as promising high-power energy storage devices due to their high power density, excellent reversibility, rapid charge and discharge, and long lifespan. A supercapacitor consists of three parts: electrodes, a separator, and an electrolyte. The performance of the device mainly depends on the electrode materials. Currently, layered cobalt-iron bimetallic hydroxide electrode materials are widely accepted for their application in supercapacitors due to their advantages such as low cost, high abundance, and environmental friendliness. However, their low specific capacitance and poor cycle stability limit their practical application.
[0003] Researchers are currently working to improve the performance of layered cobalt-iron bimetallic hydroxide electrode materials by adjusting the material composition, controlling morphology, and using ion doping. However, these methods struggle to simultaneously improve the electrode's specific capacity and charge-discharge cycle stability, preventing assembled supercapacitors from achieving a dual increase in lifespan and energy density. Therefore, there is an urgent market demand for a low-cost electrode material with high specific capacity, stable charge-discharge cycles, and a long lifespan. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for preparing composite electrode materials for supercapacitors. This invention employs a magnetic field-assisted ultrasonic-induced hydrothermal method to grow layered cobalt-iron-based hydroxides in situ on a nickel foam substrate, then combines them with graphene to prepare the electrode material. The electrode structure is optimized by integrating elemental doping, morphology control, and structural design, leveraging the synergistic effects of transition metals, dopant ions, and graphene to achieve complementarity through the intrinsic advantages of different materials. During the preparation process, the synergistic effect of multi-physics field coupling is utilized to construct nanoarrays and mesoporous structures, improving the performance of the electrode material in electrochemical reactions. Compared to existing technologies, this invention utilizes ultrasonic assistance during the growth of layered cobalt-iron-based hydroxides to promote uniform powder synthesis, reduce agglomeration, and expose more active sites, thereby improving the conductivity and specific capacitance of the electrode material. The synergistic effect of an applied alternating magnetic field induces the preferential directional growth of the layered hydroxides, allowing for the controllable synthesis of three-dimensional or hollow nanostructures, improving the specific capacitance and charge-discharge cycle stability of the electrode material. This preparation method is simple, convenient, low-cost, and easy to implement, facilitating large-scale industrial applications.
[0005] To achieve the above objectives, the present invention provides a method for preparing a supercapacitor composite electrode material, the specific steps of which are as follows:
[0006] Step 1: Preparation of a layered cobalt-iron-based hydroxide grown on nickel foam using magnetic field-assisted ultrasonic induction.
[0007] 1) The nickel foam is pretreated by degreasing with acetone, etching with HCl, and finally ultrasonically cleaned with deionized water and anhydrous ethanol to ensure surface cleanliness and dryness.
[0008] 2) Dissolve and disperse ferric nitrate nonahydrate, cobalt nitrate hexahydrate, urea and ammonium fluoride in deionized water and stir until homogeneous to obtain a solution;
[0009] 3) After the solution in step 2) is mixed evenly, add manganese chloride tetrahydrate or lanthanum chloride for doping, and stir at room temperature to obtain a mixed solution;
[0010] 4) After the mixture obtained in step 3) is stirred evenly, the reaction is carried out under ultrasonic assistance;
[0011] 5) The ultrasonically treated mixture from step 4) and the nickel foam from step 1) are transferred together into a stainless steel reactor, an external magnetic field is applied, and the mixture is reacted at a set temperature and then dried to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0012] Step 2: Preparation of a cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0013] 1) Take deionized water and graphene and stir them. After stirring evenly, put them into an ultrasonic cleaner for ultrasonic treatment to further mix the solution evenly.
[0014] 2) After the solution from step 1) is mixed evenly, add hydrazine hydrate and concentrated ammonia.
[0015] 3) Place the mixed solution from step 2) and the layered cobalt-iron-based hydroxide / nickel foam composite material obtained in step 1 into a magnetic stirrer heated to a constant temperature for reflux and constant temperature heating and stirring.
[0016] 4) Dry the sample prepared in step 3) to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
[0017] in,
[0018] In step 1), the degreasing time is 10-25 min; the concentration of HCl is 1-3 mol / L; and the etching time is 10-35 min.
[0019] In step 1, 2), the molar ratio of ferric nitrate nonahydrate to cobalt nitrate hexahydrate is (1-4):(5-1).
[0020] In step 1, 2), the molar ratio of urea to ammonium fluoride is (10-25):(4-13).
[0021] In step 1(3), the molar ratio of ferric nitrate nonahydrate to manganese chloride tetrahydrate in the solution in step 1(2) is (1-4):(0-0.5).
[0022] In step 3), the molar ratio of ferric nitrate nonahydrate to lanthanum chloride in the solution in step 2) is (1-4):(0-0.3).
[0023] In step 1(3), the reaction stirring time in step 1(2) is 30-60 min;
[0024] In step 1, 4), the ultrasonic power is 200-500W and the reaction time is 30-60min;
[0025] In step 5), the magnetic field strength is 6-14 kA / m, the alternating heating current is 20-45 A, and the magnetic field frequency is 130-190 kHz.
[0026] In step 5), the reaction temperature is 90-180℃ and the reaction time is 6-12h; the drying temperature is 60-90℃ and the drying time is 6-12h.
[0027] In step 2(1), the concentration of graphene slurry is 2-10 mg / mL; the power of the ultrasonic cleaner is 500-1000 W; and the processing time is 30-60 min.
[0028] In step 2), the volume ratio of hydrazine hydrate to concentrated ammonia is (0.5-2):(15-50).
[0029] In step 2), the mass ratio of graphene to hydrazine hydrate is (1-5):(1-3).
[0030] In step 2 (3), the temperature of the magnetic stirrer is 90-98℃, and the stirring time is 60-90 minutes.
[0031] In step 2(3), the mass ratio of layered cobalt iron-based hydroxide / foam nickel to graphene in step 2(1) is (2-3):(10-11);
[0032] In step 2 (4), the drying temperature is 60-90℃ and the drying time is 6-12h.
[0033] Compared with the prior art, the advantages of this invention are:
[0034] 1. Magnetic Field-Coordinated Ultrasonic Induction for Optimized Electrode Structure: Multi-physics composite synthesis aims to effectively control the synthesis process of layered cobalt-iron-based hydroxides through complex coupling processes, achieving a composite effect exceeding that of simple physical field superposition. An external magnetic field is used to control the orientation of layered cobalt-iron-based hydroxides, allowing for the design and controllable synthesis of three-dimensional or hollow nanostructures. By changing the direction, intensity, and frequency of the external magnetic field, the morphology and growth orientation of the hydroxides can be controlled, enhancing spin polarization and expanding the structural design space of the composite material. This results in electrode materials with stable structures, large specific surface areas, and high rate performance. The unique microenvironment cavitation bubbles generated by the ultrasonic field prevent particle aggregation, and the hierarchical nanostructures further prevent particle agglomeration, promoting the exposure of more active sites. This allows for the rapid and efficient preparation of nanocomposite materials with unique structures and excellent properties.
[0035] 2. Leveraging the Synergistic Effects of Multiple Components: Doping layered cobalt-iron-based hydroxides with metals such as manganese and lanthanum can reduce agglomeration. This induced synergistic effect allows for the regulation of the electrode material's morphology, adjusting its crystal and electronic structures, and introducing numerous defects to increase redox active sites, thereby improving the electrode material's conductivity and specific capacitance. Introducing graphene-based carbon materials further enhances conductivity, increases redox reactivity, strengthens structural stability, and extends cycle life. The synergistic effects among multiple components promote the development of a low-cost, high-specific-capacity, charge-discharge cycle-stable, and long-life electrode material.
[0036] 3. Low cost and pollution-free magnetic field-assisted ultrasonic-induced synthesis method: The preparation method provided by this invention has the characteristics of simple process, mild conditions, high reaction efficiency and low cost, short reaction time, green and pollution-free, and simple post-processing, which helps to realize large-scale industrial application. Attached Figure Description
[0037] Figure 1 This is a scanning electron microscope image of the layered cobalt iron-based hydroxide / nickel foam composite material selected in Example 1 of the present invention;
[0038] Figure 2 This is a scanning electron microscope image of the layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material selected in Example 1 of the present invention;
[0039] Figure 3 This is a cyclic voltammetry curve of the cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material in Example 1 of the present invention;
[0040] Figure 4 This is a constant current charge-discharge curve of the cobalt-iron-based hydroxide / foamed nickel / graphene composite electrode material in Example 1 of the present invention. Detailed Implementation
[0041] Unless otherwise specified, all materials used in this invention are commercially available.
[0042] The graphene slurry concentration used in this embodiment is 10 mg / mL.
[0043] Example 1
[0044] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0045] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0046] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 15min, then etching with 2mol / L HCl for 25min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and dryness.
[0047] 2) Dissolve and disperse 1 mmol ferric nitrate nonahydrate, 1.9 mmol cobalt nitrate hexahydrate, 19 mmol urea and 8 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0048] 3) Slowly add 0.1 mmol of manganese chloride tetrahydrate for doping, and stir at room temperature for 30 min to obtain a mixed solution;
[0049] 4) React for 50 minutes under 250W ultrasound assistance;
[0050] 5) The mixture and nickel foam were transferred together into a 50 mL stainless steel reactor. An external magnetic field with a strength of 12 kA / m, an alternating current of 30 A, and a magnetic field frequency of 135 kHz was applied. The mixture was reacted at 120 °C for 9 h, followed by drying at 60 °C for 6 h to obtain a layered cobalt-iron-based hydroxide / nickel foam composite material. Its scanning electron microscope image is shown below. Figure 1 As shown.
[0051] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0052] 1) Measure 50 mL of deionized water and 3 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 30 minutes to further mix the solution evenly.
[0053] 2) Add 6 mL of hydrazine hydrate and concentrated ammonia to the mixture. The volume ratio of hydrazine hydrate to concentrated ammonia is 1:30.
[0054] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 98°C constant temperature heating magnetic stirrer, and reflux and heat at a constant temperature for 60 min;
[0055] 4) The sample was removed and dried in a 60℃ oven for 12 hours to obtain a layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material, as shown in the scanning electron microscope image below. Figure 2 As shown, the cyclic voltammetry curve is as follows: Figure 3 As shown, the constant current charge-discharge curve is as follows: Figure 4 As shown.
[0056] Example 2
[0057] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0058] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0059] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 10min, then etching with 2mol / L HCl for 30min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and dryness.
[0060] 2) Dissolve and disperse 1 mmol ferric nitrate nonahydrate, 2.8 mmol cobalt nitrate hexahydrate, 18 mmol urea and 7 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0061] 3) Slowly add 0.15 mmol of lanthanum chloride for doping, and stir at room temperature for 40 min to obtain a mixed solution;
[0062] 4) React for 40 minutes under 300W ultrasound assistance;
[0063] 5) The mixture and nickel foam were transferred together into a 50mL stainless steel reactor. An external magnetic field with a strength of 10kA / m, an alternating current of 25A, and a magnetic field frequency of 140kHz was applied. The mixture was reacted at 90℃ for 12h and then dried at 60℃ for 8h to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0064] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0065] 1) Measure 50 mL of deionized water and 3 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 40 minutes to further mix the solution evenly.
[0066] 2) Add 5 mL of hydrazine hydrate and concentrated ammonia to the mixture. The volume ratio of hydrazine hydrate to concentrated ammonia is 1:30.
[0067] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 98°C constant temperature heating magnetic stirrer, and reflux and heat at a constant temperature for 70 min.
[0068] 4) The sample was taken out and placed in a 60℃ oven for drying for 12 hours to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
[0069] Example 3
[0070] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0071] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0072] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 15min, then etching with 2mol / L HCl for 30min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and dryness.
[0073] 2) Dissolve and disperse 1 mmol ferric nitrate nonahydrate, 1.7 mmol cobalt nitrate hexahydrate, 19 mmol urea and 6 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0074] 3) Slowly add 0.3 mmol of manganese chloride tetrahydrate for doping, and stir for 30 min at room temperature to obtain a mixed solution;
[0075] 4) React for 30 minutes under 350W ultrasound assistance;
[0076] 5) The mixture and nickel foam were transferred together into a 50mL stainless steel reactor. An external magnetic field with a strength of 8kA / m, an alternating current of 30A, and a magnetic field frequency of 145kHz was applied. The mixture was reacted at 100℃ for 12h and then dried at 60℃ for 6h to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0077] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0078] 1) Measure 50 mL of deionized water and 4 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 30 minutes to further mix the solution evenly.
[0079] 2) Add 5 mL of hydrazine hydrate and concentrated ammonia to the mixture, with a volume ratio of hydrazine hydrate to concentrated ammonia of 1:30;
[0080] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 95°C constant temperature heating magnetic stirrer, and reflux and heat at a constant temperature for 60 min.
[0081] 4) The sample was taken out and placed in a 60℃ oven for drying for 10 hours to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
[0082] Example 4
[0083] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0084] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0085] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 15min, then etching with 2mol / L HCl for 35min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and drying.
[0086] 2) Dissolve and disperse 2 mmol ferric nitrate nonahydrate, 1 mmol cobalt nitrate hexahydrate, 16 mmol urea and 8 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0087] 3) Slowly add 0.2 mmol of manganese chloride tetrahydrate for doping, and stir for 50 min at room temperature to obtain a mixed solution;
[0088] 4) React for 35 minutes under 350W ultrasound assistance;
[0089] 5) The mixture and nickel foam were transferred together into a 50mL stainless steel reactor. An external magnetic field with a strength of 10kA / m, an alternating current of 25A, and a magnetic field frequency of 150kHz was applied. The mixture was reacted at 120℃ for 7h and then dried at 60℃ for 6h to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0090] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0091] 1) Measure 50 mL of deionized water and 2.5 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 40 minutes to further mix the solution evenly.
[0092] 2) Add 6 mL of hydrazine hydrate and concentrated ammonia to the mixture, with a volume ratio of hydrazine hydrate to concentrated ammonia of 1:30;
[0093] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 98°C constant temperature heating magnetic stirrer and reflux for 80 min.
[0094] 4) Take out the sample and put it into a 60℃ oven for drying for 8 hours to obtain the layered cobalt iron-based hydroxide / foam nickel / graphene composite electrode material.
[0095] Example 5
[0096] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0097] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0098] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 20min, then etching with 2mol / L HCl for 30min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and dryness.
[0099] 2) Dissolve and disperse 3 mmol ferric nitrate nonahydrate, 1 mmol cobalt nitrate hexahydrate, 18 mmol urea and 8 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0100] 3) Slowly add 0.1 mmol of manganese chloride tetrahydrate for doping, and stir at room temperature for 30 min to obtain a mixed solution;
[0101] 4) React for 35 minutes under 400W ultrasound assistance;
[0102] 5) The mixture and nickel foam were transferred together into a 50mL stainless steel reactor. An external magnetic field with a strength of 8kA / m, an alternating current of 30A, and a magnetic field frequency of 150kHz was applied. The mixture was reacted at 110℃ for 8h and then dried at 60℃ for 6h to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0103] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0104] 1) Measure 50 mL of deionized water and 3 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 30 minutes to further mix the solution evenly.
[0105] 2) Add 5 mL of hydrazine hydrate and concentrated ammonia to the mixture, with a volume ratio of hydrazine hydrate to concentrated ammonia of 1:30;
[0106] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 98°C constant temperature heating magnetic stirrer, and reflux and heat at a constant temperature for 60 min;
[0107] 4) The sample was taken out and placed in a 60℃ oven for drying for 12 hours to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
[0108] Example 6
[0109] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0110] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0111] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 15min, then etching with 3mol / L HCl for 15min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and dryness.
[0112] 2) Dissolve and disperse 1 mmol ferric nitrate nonahydrate, 1.7 mmol cobalt nitrate hexahydrate, 20 mmol urea and 8 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0113] 3) Slowly add 0.3 mmol of manganese chloride tetrahydrate for doping, and stir for 30 min at room temperature to obtain a mixed solution;
[0114] 4) React for 30 minutes under 450W ultrasound assistance;
[0115] 5) The mixture and nickel foam were transferred together into a 50mL stainless steel reactor. An external magnetic field with a strength of 12kA / m, an alternating current of 25A, and a magnetic field frequency of 140kHz was applied. The mixture was reacted at 130℃ for 10h and then dried at 60℃ for 6h to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0116] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0117] 1) Measure 50 mL of deionized water and 4 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 50 minutes to further mix the solution evenly.
[0118] 2) Add 6 mL of hydrazine hydrate and concentrated ammonia to the mixture, with a volume ratio of hydrazine hydrate to concentrated ammonia of 1:30;
[0119] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 98°C constant temperature heating magnetic stirrer and reflux for 80 min.
[0120] 4) The sample was taken out and placed in a 60℃ oven for drying for 10 hours to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
[0121] Example 7
[0122] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0123] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0124] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 20min, then etching with 2mol / L HCl for 25min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and drying.
[0125] 2) Dissolve and disperse 1 mmol ferric nitrate nonahydrate, 1.8 mmol cobalt nitrate hexahydrate, 18 mmol urea and 6 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0126] 3) Slowly add 0.2 mmol of manganese chloride tetrahydrate for doping, and stir at room temperature for 40 min to obtain a mixed solution;
[0127] 4) React for 45 minutes under 300W ultrasound assistance;
[0128] 5) The mixture and nickel foam were transferred together into a 50mL stainless steel reactor. An external magnetic field with a strength of 8kA / m, an alternating current of 35A, and a magnetic field frequency of 135kHz was applied. The mixture was reacted at 110℃ for 10h and then dried at 60℃ for 6h to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0129] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0130] 1) Measure 50 mL of deionized water and 3.5 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 30 minutes to further mix the solution evenly.
[0131] 2) Add 5 mL of hydrazine hydrate and concentrated ammonia to the mixture, with a volume ratio of hydrazine hydrate to concentrated ammonia of 1:30;
[0132] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 95°C constant temperature heating magnetic stirrer, and reflux and heat at a constant temperature for 70 min;
[0133] 4) The sample was taken out and placed in a 70℃ oven for drying for 10 hours to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
[0134] Example 8
[0135] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0136] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0137] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 15min, then etching with 3mol / L HCl for 15min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and dryness.
[0138] 2) Dissolve and disperse 1 mmol ferric nitrate nonahydrate, 1.9 mmol cobalt nitrate hexahydrate, 20 mmol urea and 6 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0139] 3) Slowly add 0.1 mmol of lanthanum chloride for doping, and stir at room temperature for 30 min to obtain a mixed solution;
[0140] 4) React for 35 minutes under 350W ultrasound assistance;
[0141] 5) The mixture and nickel foam were transferred together into a 50mL stainless steel reactor. An external magnetic field with a strength of 6kA / m, an alternating current of 30A, and a magnetic field frequency of 140kHz was applied. The mixture was reacted at 100℃ for 8 hours and then dried at 60℃ for 8 hours to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0142] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0143] 1) Measure 50 mL of deionized water and 4 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 40 minutes to further mix the solution evenly.
[0144] 2) Add 5 mL of hydrazine hydrate and concentrated ammonia to the mixture, with a volume ratio of hydrazine hydrate to concentrated ammonia of 1:30;
[0145] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 98°C constant temperature heating magnetic stirrer and reflux constant temperature heating and stirring for 60 min;
[0146] 4) The sample was taken out and placed in an 80℃ oven for drying for 10 hours to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
[0147] Example 9
[0148] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0149] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0150] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 15min, then etching with 2mol / L HCl for 30min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and drying.
[0151] 2) Dissolve and disperse 1 mmol ferric nitrate nonahydrate, 1.8 mmol cobalt nitrate hexahydrate, 19 mmol urea and 8 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0152] 3) Slowly add 0.2 mmol of lanthanum chloride for doping, and stir at room temperature for 30 min to obtain a mixed solution;
[0153] 4) React for 45 minutes under 400W ultrasound assistance;
[0154] 5) The mixture and nickel foam were transferred together into a 50mL stainless steel reactor. An external magnetic field with a strength of 10kA / m, an alternating current of 25A, and a magnetic field frequency of 130kHz was applied. The mixture was reacted at 150℃ for 6h and then dried at 60℃ for 6h to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0155] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0156] 1) Measure 50 mL of deionized water and 4.5 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 30 minutes to further mix the solution evenly.
[0157] 2) Add 6 mL of hydrazine hydrate and concentrated ammonia to the mixture, with a volume ratio of hydrazine hydrate to concentrated ammonia of 1:30;
[0158] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 95°C constant temperature heating magnetic stirrer, and reflux and heat at a constant temperature for 80 min.
[0159] 4) The sample was taken out and placed in a 60℃ oven for drying for 12 hours to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
[0160] Example 10
[0161] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0162] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0163] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 15min, then etching with 2mol / L HCl for 30min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and drying.
[0164] 2) Dissolve and disperse 2 mmol ferric nitrate nonahydrate, 1.2 mmol cobalt nitrate hexahydrate, 20 mmol urea and 8 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0165] 3) Slowly add 0.15 mmol of lanthanum chloride for doping, and stir at room temperature for 30 min to obtain a mixed solution;
[0166] 4) React for 50 minutes under 250W ultrasound assistance;
[0167] 5) The mixture and nickel foam were transferred together into a 50mL stainless steel reactor. An external magnetic field with a strength of 12kA / m, an alternating current of 20A, and a magnetic field frequency of 135kHz was applied. The mixture was reacted at 120℃ for 8 hours and then dried at 60℃ for 6 hours to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0168] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0169] 1) Measure 50 mL of deionized water and 3 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 30 minutes to further mix the solution evenly.
[0170] 2) Add 6 mL of hydrazine hydrate and concentrated ammonia to the mixture, with a volume ratio of hydrazine hydrate to concentrated ammonia of 1:30;
[0171] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 98°C constant temperature heating magnetic stirrer and reflux constant temperature heating and stirring for 60 min;
[0172] 4) The sample was taken out and placed in a 70℃ oven for drying for 12 hours to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
[0173] Example 11
[0174] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0175] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0176] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 15min, then etching with 2mol / L HCl for 30min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and drying.
[0177] 2) Dissolve and disperse 2 mmol ferric nitrate nonahydrate, 1.5 mmol cobalt nitrate hexahydrate, 18 mmol urea and 8 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0178] 3) Slowly add 0.2 mmol of lanthanum chloride for doping, and stir at room temperature for 30 min to obtain a mixed solution;
[0179] 4) React for 55 minutes under 250W ultrasound assistance;
[0180] 5) The mixture and nickel foam were transferred together into a 50mL stainless steel reactor. An external magnetic field with a strength of 10kA / m, an alternating current of 20A, and a magnetic field frequency of 140kHz was applied. The mixture was reacted at 130℃ for 10h and then dried at 60℃ for 8h to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0181] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0182] 1) Measure 50 mL of deionized water and 5 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 30 minutes to further mix the solution evenly.
[0183] 2) Add 6 mL of hydrazine hydrate and concentrated ammonia to the mixture, with a volume ratio of hydrazine hydrate to concentrated ammonia of 1:30;
[0184] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 98°C constant temperature heating magnetic stirrer and reflux constant temperature heating and stirring for 60 min;
[0185] 4) The sample was taken out and placed in a 60℃ oven for drying for 10 hours to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
[0186] Example 12
[0187] A method for preparing a composite electrode material for supercapacitors, comprising the following specific steps:
[0188] Step 1: Preparation of layered cobalt-iron-based hydroxides grown on nickel foam under magnetic field-assisted ultrasonic induction
[0189] 1) Pre-treat the nickel foam (1cm×2cm) by degreasing with acetone for 15min, then etching with 2mol / L HCl for 30min, and finally ultrasonically cleaning with deionized water and anhydrous ethanol to ensure surface cleanliness and drying.
[0190] 2) Dissolve and disperse 1 mmol ferric nitrate nonahydrate, 2.7 mmol cobalt nitrate hexahydrate, 20 mmol urea and 8 mmol ammonium fluoride in 40 mL of deionized water and stir until homogeneous to obtain a solution;
[0191] 3) Slowly add 0.25 mmol of lanthanum chloride for doping, and stir at room temperature for 40 min to obtain a mixed solution;
[0192] 4) React for 45 minutes under 300W ultrasound assistance;
[0193] 5) The mixture and nickel foam were transferred together into a 50mL stainless steel reactor. An external magnetic field with a strength of 12kA / m, an alternating current of 25A, and a magnetic field frequency of 130kHz was applied. The mixture was reacted at 150℃ for 8 hours and then dried at 60℃ for 10 hours to obtain a layered cobalt iron-based hydroxide / nickel foam composite material.
[0194] Step 2: Preparation of layered cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material
[0195] 1) Measure 50 mL of deionized water and 4 mL of viscous graphene into a beaker, then stir. After stirring evenly, place the beaker into an ultrasonic cleaner with a power of 600W and sonicate for 30 minutes to further mix the solution evenly.
[0196] 2) Add 5 mL of hydrazine hydrate and concentrated ammonia to the mixture, with a volume ratio of hydrazine hydrate to concentrated ammonia of 1:30;
[0197] 3) Place the mixed solution and the layered cobalt iron-based hydroxide / nickel foam composite material prepared in step one into a 98°C constant temperature heating magnetic stirrer and reflux constant temperature heating and stirring for 60 min;
[0198] 4) The sample was taken out and placed in a 60℃ oven for drying for 12 hours to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
Claims
1. A method for preparing a composite electrode material for a supercapacitor, characterized in that, The specific steps are as follows: Step 1: Preparation of a layered cobalt-iron-based hydroxide grown on nickel foam using magnetic field-assisted ultrasonic induction. 1) The nickel foam is pretreated by degreasing with acetone, etching with HCl, and finally ultrasonically cleaned with deionized water and anhydrous ethanol to ensure surface cleanliness and dryness. 2) Dissolve and disperse ferric nitrate nonahydrate, cobalt nitrate hexahydrate, urea and ammonium fluoride in deionized water and stir until homogeneous to obtain a solution; 3) After the solution in step 2) is mixed evenly, add manganese chloride tetrahydrate or lanthanum chloride for doping, and stir at room temperature to obtain a mixed solution; 4) After the mixture obtained in step 3) is stirred evenly, the reaction is carried out under ultrasonic assistance; 5) The ultrasonically treated mixture from step 4) and the nickel foam were transferred together into a stainless steel reactor, an external magnetic field was applied, and the mixture was reacted at a set temperature and then dried to obtain a layered cobalt iron-based hydroxide / nickel foam composite material. Step 2: Preparation of a cobalt-iron-based hydroxide / nickel foam / graphene composite electrode material 1) Take deionized water and graphene and stir them. After stirring evenly, put them into an ultrasonic cleaner for ultrasonic treatment to further mix the solution evenly. 2) After the solution from step 1) is mixed evenly, add hydrazine hydrate and concentrated ammonia. 3) Place the mixed solution from step 2) and the layered cobalt-iron-based hydroxide / nickel foam composite material obtained in step 1 into a magnetic stirrer heated to a constant temperature for reflux and constant temperature heating and stirring. 4) Dry the sample prepared in step 3) to obtain a layered cobalt iron-based hydroxide / nickel foam / graphene composite electrode material.
2. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that, In step 1), the degreasing time is 10-25 min; the concentration of HCl is 1-3 mol / L; and the etching time is 10-35 min.
3. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that, In step 1(2), the molar ratio of ferric nitrate nonahydrate to cobalt nitrate hexahydrate is (1-4):(5-1), and the molar ratio of urea to ammonium fluoride is (10-25):(4-13).
4. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that, In step 1(3), the molar ratio of ferric nitrate nonahydrate to manganese chloride tetrahydrate in the solution in step 1(2) is (1-4):(0-0.5), and the molar ratio of ferric nitrate nonahydrate to lanthanum chloride is (1-4):(0-0.3); the reaction stirring time is 30-60 min.
5. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that, In step 1(4), the ultrasonic power is 200-500W and the reaction time is 30-60min.
6. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that, In step 5), the magnetic field strength is 6-14 kA / m, the alternating heating current is 20-45 A, the magnetic field frequency is 130-190 kHz, the reaction temperature is 90-180℃, the reaction time is 6-12 h, the drying temperature is 60-90℃, and the drying time is 6-12 h.
7. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that, In step 2(1), the graphene slurry concentration is 2-10 mg / mL; the ultrasonic cleaner power is 500-1000 W; and the treatment time is 30-60 min.
8. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that, In step 2), the volume ratio of hydrazine hydrate to concentrated ammonia is (0.5-2):(15-50), and the mass ratio of graphene to hydrazine hydrate is (1-5):(1-3).
9. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that, In step 2(3), the temperature of the magnetic stirrer is 90-98℃ and the stirring time is 60-90min; the mass ratio of layered cobalt iron-based hydroxide / foam nickel to graphene in step 2(1) is (2-3):(10-11).
10. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that, In step 2 (4), the drying temperature is 60-90℃ and the drying time is 6-12h.
Citation Information
Patent Citations
Novel hydrothermal template agent of graphene oxide and preparation method of nanocomposite material of novel hydrothermal template agent
CN107098341A
Method for manufacturing electrode material, cell, and capacitor; and device for manufacturing electrode material
US20180301291A1